Faktor Intrinsik yang Berperan pada Motivasi Kerja dari Perspektif Teori Dua Faktor pada CO BTPNS - Halimatussadiah Halimatussadiah; Zulfina Adriani; Dian Mala Fithriani Aira (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
Work motivation is crucial in enhancing employee performance and productivity, especially in the Islamic banking sector. This study analyzes intrinsic factors influencing the work motivation of Community Officers at Bank BTPN Syariah MMS Rantau Rasau based on Herzberg’s Two-Factor Theory. Using a descriptive qualitative approach, data was collected through interviews, observations, and document analysis. The findings reveal that intrinsic factors contributing to motivation include achievement, recognition, responsibility, the nature of the work, and career development opportunities. Among these, achievement and recognition are the most dominant factors influencing work motivation. Community Officers who receive appreciation for their achievements and recognition from superiors and colleagues tend to demonstrate higher morale and commitment. Therefore, this study recommends that Bank BTPN Syariah emphasize achievement and recognition in human resource management policies. Providing rewards for accomplishments and constructive feedback can enhance employee motivation and performance, ultimately supporting organizational goals.